2019
DOI: 10.1109/jsen.2019.2939555
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light Coupling Configuration and Alignment on the Stability of HWG-Based Gas Sensor System for Real-Time Detection of Exhaled Carbon Dioxide

Abstract: A mid-infrared tunable diode laser absorption 2 spectroscopy (TDLAS) gas sensor based on hollow waveguide 3 (HWG) gas cell for real-time exhaled carbon dioxide (eCO2) 4 detection is reported. A 2.73 μm distributed feedback (DFB) laser 5 was used to target a strong CO2 absorption line, and wavelength 6 modulation spectroscopy (WMS) with the second harmonic 7 (WMS-2ƒ) was used to retrieve the CO2 concentration with high 8 sensitivity. The influence of different parameters, including 9 coupling configuration of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hence, the aperture of diaphragm is set to 1 mm. Apart from that, the influences of in-coupling (position of the laser related to the HWG) and out-coupling (position of the detector related to the HWG) on system stability are also investigated [24]. The laser was placed at the central position for long stability time.…”
Section: Optimization Of System Parametersmentioning
confidence: 99%
“…Hence, the aperture of diaphragm is set to 1 mm. Apart from that, the influences of in-coupling (position of the laser related to the HWG) and out-coupling (position of the detector related to the HWG) on system stability are also investigated [24]. The laser was placed at the central position for long stability time.…”
Section: Optimization Of System Parametersmentioning
confidence: 99%
“…Characterized by high sensitivity, high resolution, and fast response, tunable diode laser absorption spectroscopy (TDLAS) is extensively employed in industrial process gas analysis [1,2], environmental monitoring [3,4], and biomedical science [5][6][7]. TDLAS technology can be roughly divided into direct absorption spectroscopy (DAS) and wavelength modulation spectroscopy (WMS).…”
Section: Introductionmentioning
confidence: 99%
“…Hollow waveguide (HWG) can miniaturize TLAS gas sensors with very small sampling volume and fast response time, which has been widely used as a novel gas cell recently. 10,19 In our previous work, we have quantitatively investigated the adsorption effect of ammonia gas molecules on the inner surface of Ag/AgI coated HWG, 20 the of transmission loss property of semiconductor laser beam propagating in the HWG, 21 and the effects of gas flow regimes on the complicated spectral line broadening in HWGs. 22 Based on the above research, HWG enhanced TLAS gas sensors have been developed and demonstrated for atmospheric environment monitoring 23 and exhaled breath analysis.…”
Section: Introductionmentioning
confidence: 99%